Audit of buying patterns of drugs from various pharmacies in Northern India - Chawla, Shalini; Agarwal, Monika; Arora, Ayush (International Journal of Basic & Clinical Pharmacology, 2017)
A study was conducted to gather data regarding drug buying practices in Delhi to compare the same in rural pharmacies in surrounding area. A cross sectional study was conducted as exit interviews using pretested Performa with customers visiting randomly selected pharmacies of Delhi and rural Haryana. Out of 280 consumers interviewed 140 belonged to urban areas and 140 to rural areas. In both areas male and younger consumers are significantly high. Most consumers in both set ups took medication after physician’s prescription in comparison to self medication. Source of information for self medication was media in urban and friends in rural areas. Alteration in brand name was more in rural areas. Antimicrobials and NSAIDs in rural areas and drugs for cardiovascular diseases and oral hypoglycemic drugs in urban areas are major purchased drug groups.